COMPARISON OF CONSTITUTIONAL COURT AUTHORITY BETWEEN INDONESIA AND SOUTH KOREA - Janpatar Simamora (Jurnal Dinamika Hukum, 2015)
This paper is intended to find out the comparison between Indonesian and South Korea constitutional court. Constitutional Court of Indonesia and South Korea have same authority, namely judicial review, the authority decide the disputes between state institutions and the dissolution of political parties. However, there are some differences. From the point of authority, Constitutional Court of Korea is more comprehensive because it has the constitutional complaint authority and in deciding the dispute of state institutions authority, the dispute type of the state institutions authority is classified explicitly. But fromthe point of judicial review execution, the constitutional court in Indonesia is more comprehensive because the applicant could be more flexible. Indonesian Constitutional Court should be able to adopt the excellence of Constitutional Court of Korea while maintaining it’s excellence to maximize the Constitutional Court as escort agencies and  interpreter of the Constitution.Keywords: Indonesia, authority, South Korea, constitutional court.